(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
The article talks about the need to improve the culture of communication among managers of the management system at the stage of development of society, about the effectiveness of the reforms carried out in the country, which depend, first of all, on the level of management personnel; one of the most important requirements is mastering the skills of public speaking, the ability to use the power of the living word.